2011
DOI: 10.1258/jhsrp.2010.009053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ‘Success’ In Programme Budgeting and Marginal Analysis: A Literature Review

Abstract: The rate of success is clearly influenced by how success is defined. There is a need for a broadly accepted definition of success to be used when evaluating PBMA applications so to enable direct comparisons of studies. This evaluatory component needs to be adjacent to PBMA and not a separate procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
(67 reference statements)
0
44
0
Order By: Relevance
“…As noted by a recent systematic review, the success of PBMA depends in part on how its impact is measured, that is, in improved understanding, implemented recommendations, disinvestment from specific services or technologies, or adoption of the PBMA framework for future use 58. While challenges remain in prioritising between sectors, enacting investment and disinvestment recommendations, and overcoming perceptions that PBMA is ‘data hungry’ (table 1), PBMA offers a useful planning method for shifting resource utilisation and identifying savings which may assist in offsetting the costs of transformation.…”
Section: Resultsmentioning
confidence: 99%
“…As noted by a recent systematic review, the success of PBMA depends in part on how its impact is measured, that is, in improved understanding, implemented recommendations, disinvestment from specific services or technologies, or adoption of the PBMA framework for future use 58. While challenges remain in prioritising between sectors, enacting investment and disinvestment recommendations, and overcoming perceptions that PBMA is ‘data hungry’ (table 1), PBMA offers a useful planning method for shifting resource utilisation and identifying savings which may assist in offsetting the costs of transformation.…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, the National Institute for Clinical Excellence has already mandated the preemptive referral to the cardiothoracic team for all ICTT in at least one region (to Wythenshawe Hospital, Manchester, UK). A streamlined procedure plan would be especially advantageous if technical performance was to be scored [52] in order to convince the stakeholders where the local setup is reluctant to change [16]; a marginal analysis [53] would recommend reallocating resources to increase efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…To date there has been little consistent or coherent attention given to evaluation of priority setting and resource allocation processes [2,28]. Sibbald et al's framework is groundbreaking in this sense [29,30].…”
Section: Overall Assessment Of Resource Allocation Processesmentioning
confidence: 99%
“…There are some priority setting or resource allocation case studies reported in the literature, though as Tsourapas & Frew [2] note, only one macro-level case-that is an organization-wide effort to allocate between different Departments and types of services [3]-has been widely reported [Calgary, 2001[Calgary, -2003. While some of the authors have been involved in other projects at this level in Canada only one has yet been reported in the peer reviewed literature [4,5].…”
Section: Introductionmentioning
confidence: 99%